Objective Tyre Development : Definition and Analysis of Tyre Characteristics and Quantification of their Conflicts - Peckelsen, Ulrico (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2017)
The present work focuses on tyres for passenger cars, especially on its influence on power loss, lateral dynamics, ride comfort and interior noise. The objective of the work is the quantification of conflicts between four selected requirements considering the physical constraints given by the tyre. The method proposed in the present book is based on a set of functional tyre characteristics, a physical tyre model and a procedure for identifying and quantifying the conflicts.